Prosedur Audit Sewa PSAK 116 Pada PT. X - Poppy Yana Mia Nabila; Galuh Artika Febriyanti (ITB AAS INDONESIA, 2025)
The implementation of Financial Accounting Standards Statement (PSAK) 116, formerly known as PSAK 73, which came into effect in Indonesia on January 1, 2020, marked a significant shift in the accounting treatment of lease transactions. Unlike the previous PSAK 30, which only required recognition of finance leases on the balance sheet, PSAK 116 mandates the recognition of all lease transactions—both operating and finance leases—in financial statements. The primary goal of this standard is to enhance transparency of long-term obligations, such as lease liabilities, which were previously unrecorded. This allows stakeholders to gain a clearer picture of a company’s financial position. This study aims to analyze the audit procedures for building leases at PT X and to assess whether the company has applied PSAK 116 accurately in its financial reporting. Data were collected through interviews with senior auditors, documentation of lease contracts, and literature review. The findings show that PT X has applied PSAK 116 since 2022; however, in 2024, lease transactions were no longer recorded in accordance with the standard. The implementation of PSAK 116 significantly increased the company’s reported assets and liabilities, thereby improving the relevance and transparency of its financial statements.